Comparing expert and public perceptions of the obesity epidemic in 3 countries - Deirdre A. Robertson; Ylva Andersson; Ciarán Lavin; Pete Lunn (The Economic and Social Research Institute (ESRI), 2023)
The "obesogenic environment" contributes to the global obesity epidemic. However, many believe that obesity is caused solely by individual choice. This paper investigates how the public in Ireland, the UK, and USA perceive the causes, consequences and severity of obesity compared to an expert sample. We describe an experiment to assess whether describing the obesity within its historical context brings public perceptions closer to experts. We find significant differences between expert and public views and between countries. The experiment was effective, but effects were small. The paper discusses obstacles to acceptable policies to reduce rates of obesity in Ireland.
Keywords: 330; Obesity; Overweight; Perceptions; Behaviour; Environment; Obesogenic; Attitudes; Policy